O ranelato de estrôncio reduz dor articular e dano estrutural em artrite experimental por um mecanismo dependente de citocinas - Sampaio, Leonardo Ribeiro (2012)
Strontium ranelate (SR) is a compound currently used to treat osteoporosis that, similar to bisphosphonates, may also provide analgesia. We aim to investigate the anti-inflammatory activity of SR in zymosan arthritis and in the anterior cruciate ligament transection (ACLT) osteoarthritis (OA) model. Rats received 1 mg zymosan intra-articularly or saline into the knee. Other groups were subjected to ACLT or a sham procedure. Hypernociception (joint pain) was assessed using the articular incapacitation and paw-pressure tests. Cell influx and cytokines were measured in joint exudates and OA severity was evaluated using histopathology 70 days after ACLT. Groups received either SR (30 – 300 mg/kg per os) or saline. SR dose-dependently and significantly inhibited joint pain in both arthritis models, while not altering cell influx. Chronic daily administration of the same dose of SR (300 mg/kg) that was antihypernociceptive significantly reduced OA severity at histopathology. Joint levels of IL-1β and TNF measured in the acute phase of zymosan arthritis were significantly reduced by SR, whereas those of CINC-1 were not altered. This is the first report that SR provides analgesia in two arthritis models. Additionally, daily administration of SR prevented joint damage in an OA model. These effects are associated to inhibition of inflammatory cytokines release into the inflamed joints. In addition to demonstrate that SR may operate through a cytokine-dependent mechanism, these results suggest a potential disease-modifying effect of SR in OA.